2019
DOI: 10.1038/s41598-019-42456-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell-penetrating peptide sequence and modification dependent uptake and subcellular distribution of green florescent protein in different cell lines

Abstract: Protein therapy holds great promise for treating a variety of diseases. To act on intracellular targets, therapeutic proteins must cross the plasma membrane. This has previously been achieved by covalent attachment to a variety of cell-penetrating peptides (CPPs). However, there is limited information on the relative performance of CPPs in delivering proteins to cells, specifically the cytosol and other intracellular locations. Here we use green fluorescent protein (GFP) as a model cargo to compare delivery ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
157
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(179 citation statements)
references
References 32 publications
9
157
0
4
Order By: Relevance
“…The eluted proteins were concentrated into phosphate buffered saline (PBS) and analyzed for purity by polyacrylamide gel electrophoresis (PAGE) (Supplemental Figure S2) prior to cell treatments. In addition to the expected product (~46.2 kDa), we observed two additional smaller bands (Supplemental Figure S2) that suggested cleavage of a portion of the protein, which has been observed for overexpressed recombinant proteins in certain E. coli strains [25] . Cultured U-2 OS cells treated with 0.2 μM purified CP-PcTF showed much stronger cellular red fluorescent signal after 24 hours than cells treated with PcTF that lacked the TAT signal ( Figure 2A).…”
Section: -D Culturessupporting
confidence: 56%
See 1 more Smart Citation
“…The eluted proteins were concentrated into phosphate buffered saline (PBS) and analyzed for purity by polyacrylamide gel electrophoresis (PAGE) (Supplemental Figure S2) prior to cell treatments. In addition to the expected product (~46.2 kDa), we observed two additional smaller bands (Supplemental Figure S2) that suggested cleavage of a portion of the protein, which has been observed for overexpressed recombinant proteins in certain E. coli strains [25] . Cultured U-2 OS cells treated with 0.2 μM purified CP-PcTF showed much stronger cellular red fluorescent signal after 24 hours than cells treated with PcTF that lacked the TAT signal ( Figure 2A).…”
Section: -D Culturessupporting
confidence: 56%
“…These differences in subcellular distribution might affect the gene-regulating activity of the PcTF protein. Furthermore, PAGE analysis of purified CP-PcTF showed that at least half of the total protein may have been cleaved by endogenous protease activity in E. coli , [25] . Therefore, a substantial portion of CP-PcTF may have been truncated prior to delivery.…”
Section: Rna-seq Analysis Of Cp-pctf-treated Cells Showed Modest Effementioning
confidence: 99%
“…Delivery of proteins to endosomes and lysosomes can be easily and efficiently achieved, even if proteins often cannot escape from endosomes [65,66]. How can antibodies be employed for therapy in these compartments?…”
Section: Antibody Delivery Routes: Endosomes Lysosomes Er-associatementioning
confidence: 99%
“…[8][9][10] For example, several CPPs have been genetically fused to the N-or C-terminus of an otherwise impermeable protein to render the latter cell-permeable. [11][12][13][14] An attractive feature of CPP-mediated protein delivery is that CPPs are relatively tolerant to the physicochemical properties of the cargo, which are highly diverse among different proteins. However, linear CPPs generally have low cytosolic delivery efficiencies (<5%).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some of the fusion proteins are so unstable that they cannot be isolated from bacterial expression systems in their intact forms. 14 Several other approaches are also being pursued to deliver recombinant proteins into mammalian cells, including physical methods, 17 fusion with bacterial toxins, 18 surface modification, [19][20][21] complexation with cationic peptides and polymers, [22][23][24][25] and encapsulation into nanoparticles and liposomes. 26,27 Each of these approaches has its advantages but also faces unique challenges.…”
Section: Introductionmentioning
confidence: 99%